Brain organoids: Establishment and application - Chen, Hao; Jin, Xin; Li, Tie; Ye, Zhuang (Frontiers in Cell and Developmental Biology, 2022)
Brain organoids are produced by the differentiation of pluripotent stem cells under three-dimensional culture conditions by adding neurodevelopment-related regulatory signals. They are similar to the cell composition and anatomical structure of the brain, and can reflect the developmental process of the brain, as well as their physiology, pathology, and pharmacology. Brain organoids are good models to study human brain development and brain-related diseases in vitro. Here, we mainly focus on the construction of brain organoids and review the application of brain organoids in disease modelingand drug screening.